2018
DOI: 10.1186/s13046-018-0750-2
|View full text |Cite
|
Sign up to set email alerts
|

The dual blockade of MET and VEGFR2 signaling demonstrates pronounced inhibition on tumor growth and metastasis of hepatocellular carcinoma

Abstract: BackgroundThe application of VEGF signaling inhibitors have been associated with more invasive or metastatic behavior of cancers including hepatocellular carcinoma (HCC). We explored the contribution of MET pathway to the enhanced HCC invasion and metastasis by VEGF signaling inhibition, and investigated the antitumor effects of NZ001, a novel dual inhibitor of MET and VEGFR2, in HCC.MethodsImmunocompetent orthotopic mice model of hepal-6 was established to investigate the effects of either VEGF antibody alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…The main mechanisms of drug resistance to sorafenib include the activation of PI3K/Akt or Met signaling pathways [27][28][29][30][31]. Therefore, the Met kinase inhibitor, such as foretinib, has been suggested as a treatment option after sorafenib resistance in HCC patients [25,32]. Our data showed that inhibition of SAAL1 expression could lead to a reduction in HGF-induced PI3K/Akt/mTOR phosphorylation cascade.…”
Section: Inhibition Of Saal1 Significantly Increases Chemosensitivitymentioning
confidence: 75%
“…The main mechanisms of drug resistance to sorafenib include the activation of PI3K/Akt or Met signaling pathways [27][28][29][30][31]. Therefore, the Met kinase inhibitor, such as foretinib, has been suggested as a treatment option after sorafenib resistance in HCC patients [25,32]. Our data showed that inhibition of SAAL1 expression could lead to a reduction in HGF-induced PI3K/Akt/mTOR phosphorylation cascade.…”
Section: Inhibition Of Saal1 Significantly Increases Chemosensitivitymentioning
confidence: 75%
“…Moreover, the intact and normal HGF/c-Met signaling is elementary for sustaining normal redox homeostasis and could suppress tumor in the N-nitrosodiethylamine-induced HCC (Takami et al, 2007). Additionally, c-Met may induce VEGF-A expression, which can enhance tumor angiogenesis Zhang et al, 2018b).…”
Section: Onsetmentioning
confidence: 99%
“…This may provide an explanation for why the RAM add-on therapy did not provide significantly prolonged median OS and PFS rates in some clinical trials. Zhang et al [ 36 ] demonstrated that the inhibition of both VEGFR-2 and MET yielded a more promising effect on suppressing tumor growth and metastasis in hepatocellular carcinoma than blocking VEGFR-2 did. This may provide evidence for further therapy approaches for the combination medication of VEGFR-2 and MET inhibition.…”
Section: Discussionmentioning
confidence: 99%